ChemInform Abstract: Palladium‐Catalyzed Intramolecular Oxidative C—H Sulfuration of Aryl Thiocarbamates. Issue 7 (29th January 2015) - Zhao, Yingwei; Xie, Yinjun; Xia, Chungu; Huang, Hanmin
Abstract A new synthesis from thiocarbamates to benzoxathiol‐2‐ones is developed.